2019
DOI: 10.3847/2041-8213/ab40c9
|View full text |Cite
|
Sign up to set email alerts
|

Dragonfly Imaging of the Galaxy NGC 5907: A Different View of the Iconic Stellar Stream

Abstract: In 2008 it was reported that the stellar stream of the edge-on spiral NGC 5907 loops twice around the galaxy, enveloping it in a giant corkscrew-like structure. Here we present imaging of this iconic object with the Dragonfly Telephoto Array, reaching a 1σ surface brightness level of µ g = 30.3 mag arcsec −2 on spatial scales of 1 (the approximate width of the stream). We find a qualitatively different morphology from that reported in the 2008 study. The Dragonfly data do not show two loops but a single curved… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
23
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 49 publications
(50 reference statements)
2
23
0
Order By: Relevance
“…In Figure 2 we compare the relevant part of our image with the Dragonfly g-band image taken by van Dokkum et al (2019). The shape of the stream detected by us and by van Dokkum et al (2019) are identical, which is also apparent when blinking the two images. So where should the double loop reside?…”
Section: Sian Blur What Low-surface Brightness Features Does It Reveal?mentioning
confidence: 70%
See 1 more Smart Citation
“…In Figure 2 we compare the relevant part of our image with the Dragonfly g-band image taken by van Dokkum et al (2019). The shape of the stream detected by us and by van Dokkum et al (2019) are identical, which is also apparent when blinking the two images. So where should the double loop reside?…”
Section: Sian Blur What Low-surface Brightness Features Does It Reveal?mentioning
confidence: 70%
“…The recent paper by van Dokkum et al (2019) has stirred a controversy which has been hotly debated at conferences and on social media. To shed light on the discussion, we have independently taken deep data using a 1.4 meter telescope to assess whether there is a double loop structure as found by Martínez-Delgado et al (2008) or rather a simple knee-shaped stream as found by van Dokkum et al (2019). Our imaging is consistent with the latter, with no signs of a double loop.…”
Section: Discussionmentioning
confidence: 99%
“…The pitfalls of deep imaging are illustrated by the recent controversy about the tidal streams of the Splinter Galaxy, NGC 5907. Several amateur observers equipped by small telescopes have observed the streams warping the galaxy multiple times -the refereed example is Martínez-Delgado et al (2008) -while the professional astronomers with bigger telescopes were able to detect only a part of this structure (Laine et al 2016;van Dokkum et al 2019;Müller et al 2019c;Alabi et al 2020). The case remains unresolved.…”
mentioning
confidence: 99%
“…NGC 4565 is the first galaxy in the DEGS sample to be observed, and was observed for significantly longer than typical DEGS targets. The first typical DEGS galaxy to be reduced, NGC 5907, is presented in van Dokkum et al (2019). We observed NGC 4565 over 64 nights from Spring 2015 to Summer 2017.…”
Section: Observations and Data Reductionmentioning
confidence: 95%